Tartaric acid induced conversion of protopanaxadiol to ginsenosides Rg3 and Rg5 and their in situ recoveries by integrated expanded bed adsorption chromatography. Issue 15 (8th July 2016) - Huang, Dan; Li, Yang; Zhang, Min; Ruan, Shengli; Zhang, Hongyang; Wang, Yuerong; Hu, Ping
Abstract : Panax ginseng has been applied in traditional Chinese medicine for over 2000 years. It is still one of the most popular herbs in recent decades. The prescribed ginseng‐containing medicines consist of protopanaxadiol and protopanaxatriol ginsenosides, which are the major constituents of the herb. Minor ginsenosides at low levels in the herb, such as Rg3 and Rg5, have attracted more rising attention than the major ones. The existing approaches to prepare Rg3 and Rg5 usually rely on either steamed red ginseng as the source or chemical/enzymatic conversion of protopanaxadiol to the targets. It is still highly desirable to effectively achieve such minor components. In this paper, a method integrated extraction of protopanaxadiol and conversion of it to Rg3 and Rg5 has been proposed. Protopanaxadiol was extracted and simultaneously converted to Rg3 and Rg5 byd, l ‐tartaric acid. The targets were absorbed by resins on expanded bed adsorption chromatography and were then separated from other ginsenosides in different stages. Compared with conventional methods, the developed process has advantages in shortening time consumption and improving the conversion ratio of protopanaxadiol, which is promising in directly achieving Rg3 and Rg5 from P . ginseng.